PROFIL KEMAMPUAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) GURU DI SDI WAHID HASYIM MALANG - Chandra Vitasari; Anwar Sa’dullah; Mohammad Afifulloh (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
At this time life has entered the modern era where the use of technology in carrying out daily life has become an obligation, including in the world of education. The teacher is one of the important aspects in the ongoing learning process. Teachers are one of the parties who play a role in realizing quality education. Therefore, the quality of teachers greatly determines the quality of the implementation of learning in schools. Technological Pedagogical And Content Knowledge is the knowledge needed to integrate technology in learning. This type of research is descriptive research with a quantitative approach. Descriptive research is a type of research that is used to describe facts and phenomena as they are. This study tries to describe the TPACK profile of teachers at SDI Wahid Hasyim Malang, where the TK component has an average score of 14.83 with good standards. The PK component has an average score of 19.33 with sufficient criteria. The CK component has a mean score of 16 with good criteria. The PCK component obtained an average score of 16.66 with a good standard. The TPK component has an average score of 13.16 with a good standard. The TCK component has an average score of 15.66 with very good criteria. The TPACK component obtained an average score of 18.16 with very good criteria. This description shows that the TPACK ability for SDI Wahid Hasyim Malang teachers in almost all aspects of TPACK is at a good standard, except for the Pedagogic Knowledge (PK) aspect with adequate standards. Keywords: Profile, TPACK, Teachers.